5 Cold tolerant and flood tolerant breeding lines are under national evaluation for release in Madagascar - CGIAR Research Program on Rice (2020)
The advance sub 1 introgressed breeding lines have are evaluated in multiple locations for flood tolerance and through PVS process five candidate lines were identified. The candidate breeding lines have high yielding capacity and earliness by 2 weeks. They are now under evaluation for SOC to confirm their release.